Book Review: The Untold Story of Zama Zama Miners in South Africa: Unearthing Hope (Clinical Sociology Review, 2025)
Bester starts the telling of her story of South Africa’s Zama Zama miners at some miserable holes in the ground outside a dusty little town called Stilfontein. It was here, in 2025, that the issue of Zama Zama mining finally erupted forcefully into the consciousness of just about every South African, and indeed, many others the world over. Before this, the issue had kind of bubbled away just beneath the surface of popular consciousness, sometimes showing us a hint of its existence, but never really materialising fully. I return to this choice as an opening scene, the ‘scene of the crime’ to all but the most critical of observer, a little later in this reflection. But for now, the point I want to make about this is that, while this was where Bester chose to start telling the story, it is quite clear that her engagement with Zama Zama miners and mining started long before the Stilfontein frenzy. I emphasize this up front so that there can be no confusion that this book might have been an opportunistic response to the media frenzy that ‘went down’ outside Stilfontein.